CULTURAL HYBRIDITY IN PRESERVING THE MACAPAT TRADITION - KUSUMA, IRAWINNE RIZKY WAHYU; Suastra, I Made; Amanda Gelgel, Ni Made Ras; Wardi, I Nyoman; Fadlly, Harits; ., Mashuri (E-Journal of Cultural Studies, 2025)
There is a phenomenon of urgency in the local cultural order, which causes the interaction between traditional values ??and cultural influences to become stronger. Globalization can accelerate the hybridization process, but it is feared that it will give rise to new challenges. The role of mass media is very large in ultimately creating popular culture, popular culture in each era determines the formation of hybridity. The theories used and relevant according to the research focus to answer research questions are Cultural Hybridation (Bhaba). This study aims to explore the hybridity of macapat culture in the form of presentation of the macapat tradition so that it becomes an art with a hybrid identity. So, the research question is formulated as follows: How is the hybridity of the macapat tradition in the special region of Yogyakarta? This research used the qualitative data gathered from primary and secondary sources, in order to critically examine the issue of cultural hybridity in Macapat communities Yogyakarta. Keywords : Macapat Tradition, Community, Cultural Hybridity